MODEL BERMAIN BALON DALAM PERMAINAN BOLA VOLI UNTUK MENINGKATKAN HASIL BELAJAR PASSING ATAS SISWA KELAS VIa - Yustal Yustal (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
This study is encouraged by the low marks of grade VIa students at SDN 21 Batang Anai in Sport subject, especially in playing volley ball. Students used to face difficulties in doing basic technique like upper passing. This study is aimed to improve students’ learning achievement in doing upper passing by implementing playing balloon model. This is a class action research with two cycles. Data were collected through observation and test. Result of this study shows that paying balloon model can improve students’ learning achievement in doing upper passing in volley ball learning. In cycle I, average score of students is 69.2 and increase in cycle II with average score of 80.5.